Indonesia's Selective Policy Against Illegal Immigrants In The Framework Of Asean Cooperation - Respati Triana Putri; Nanda Bayu Pamungkas (Polteknik Imigrasi, 2020)
The chaos that has occurred in several countries has resulted in population displacement aimed at finding new safe and conducive places to live. For example, this chaos is like war, bloody conflict, genocide, and so on. So that many people from conflict countries migrate to other countries to achieve a better standard of living. However, sometimes they do the migration without following the procedure or they are called illegal immigrants. Indonesia is one of the developing countries and transit countries where the geographical condition of Indonesia which is in the form of an archipelago makes access to and out of the country more freely and open. With this, the potential for transnational (transnational) crime increases. The potential of the Indonesian state in the occurrence of transnational crimes is an interesting matter to discuss. In this paper, the authors use normative legal research methods with qualitative data collection juxtaposed with descriptive analysis techniques so that the existing problems regarding transnational crimes can be presented comprehensively and informatively. So to deal with this problem, countries in ASEAN are demanded to be able to play an active role in taking preventive steps to prevent and minimize transnational crime in ASEAN countries and Indonesia.